Mathematical Modeling of Protein Misfolding Mechanisms in Neurological Diseases: A Historical Overview - Carbonell, Felix; Iturria-Medina, Yasser; Evans, Alan C. (Frontiers in Neurology, 2018)
Protein misfolding refers to a process where proteins become structurally abnormal and lose their specific 3-dimensional spatial configuration. The histopathological presence of misfolded protein (MP) aggregates has been associated as the primary evidence of multiple neurological diseases, including Prion Diseases, Alzheimer Disease (AD), Parkinson Disease (PD) and Creutzfeldt-Jacob-Disease (CJD). However, the exact mechanisms of MP aggregation and propagation, as well as their impact in the long-term patient’s clinical condition is still not well understood. With this aim, a variety of mathematical models has been proposed for a better insight into the kinetic rate laws that govern the microscopic processes of protein aggregation. Complementary, another class of large-scale models rely on modern molecular imaging techniques for describing the phenomenological effects of MP propagation over the whole brain. Unfortunately, those neuroimaging-based studies do not take full advantage of the tremendous capabilities offered by the chemical kinetics modeling approach. Actually, it has been barely acknowledged that the vast majority of large-scale models have foundations on previous mathematical approaches that describe the chemical kinetics of protein replication and propagation. The purpose of the current manuscript is to present a historical review about the development of mathematical models for describing both, microscopic processes that occur during the MP aggregation and large-scale events that characterize the progression of neurodegenerative MP-mediated diseases.